1996
DOI: 10.1007/bf02199806
|View full text |Cite
|
Sign up to set email alerts
|

A peptide encoded by the human MAGE3 gene and presented by HLA-1344 induces cytolytic T lymphocytes that recognize tumor cells expressing MAGE3

Abstract: The human MAGE3 gene is expressed in a significant proportion of tumors of various histological types, but is silent in normal adult tissues other than testis and placenta. Antigens encoded by MAGE3 may therefore be useful targets for specific antitumor immunization. Two antigenic peptides encoded by the MAGE3 gene have been reported previously. One is presented to cytolytic T lymphocytes (CTL) by HLA-A1, the other by HLA-A2 molecules. Here we show that MAGE3 also codes for a peptide that is presented to CTL b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 37 publications
2
22
1
Order By: Relevance
“…Likewise, the amount of peptide needed for half-maximal lysis by this CTL line could not be determined. An M3-167 specific CTL clone, 346/8, has been obtained from a different, B*4403+ healthy donor LB822 (Herman et al, 1996). Here we independently confirmed that this clone specifically recognized M3-167/B*4403 complexes both on incubation of B*4403+/MAGE-3-target cells with synthetic peptide M3-167 and after endogenous processing in B*4403+ /MAGE-3+ melanoma cells (Fig.…”
Section: In Vitro Stimulation Of Cd8+ T Cells With Mace-3-encoded Pepsupporting
confidence: 60%
See 2 more Smart Citations
“…Likewise, the amount of peptide needed for half-maximal lysis by this CTL line could not be determined. An M3-167 specific CTL clone, 346/8, has been obtained from a different, B*4403+ healthy donor LB822 (Herman et al, 1996). Here we independently confirmed that this clone specifically recognized M3-167/B*4403 complexes both on incubation of B*4403+/MAGE-3-target cells with synthetic peptide M3-167 and after endogenous processing in B*4403+ /MAGE-3+ melanoma cells (Fig.…”
Section: In Vitro Stimulation Of Cd8+ T Cells With Mace-3-encoded Pepsupporting
confidence: 60%
“…CTLs specific for this peptide were able to rccognizeMAGE-3+ /HLA-B44' melanoma cells, indicating that M3-167 is naturally processed and presented by melanoma cells (Fig. 2 and Herman et al, 1996). This is further suggested by the observation that the amount of peptidc required for half-maximal lysis of peptide-pulsed target cells by CTL clone 346/8 is relatively low (Fig.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Many antigenic peptides presented to CTL by HLA class I molecules have been identified in the MAGE-A proteins. For instance, five antigenic peptides, presented by HLA-A1, A2, A24, or B44 are derived from the MAGE-A3 protein, and one peptide presented by HLA-A2 is derived from MAGE-A4 (Celis et al, 1994;Gaugler et al, 1994;Herman et al, 1996;Tanaka et al, 1997;van der Bruggen et al, 1994).…”
mentioning
confidence: 96%
“…Cancer/testis antigens (CTA), a series of tumor associated antigens, are exclusively expressed in diverse tumor entities [15] but silent in normal tissues except for testicular germ cells and placenta [16][17][18]. Due to the restricted expression pattern and their capability to elicit immune responses, CTAs are counted as ideal targets for immunotherapy in human malignancy [19][20].…”
mentioning
confidence: 99%